Student-Athletes' Religious Beliefs, Religious Behaviors, and Religious Identity at a Christian University. Issue 4 (2nd October 2022) - Allen, Daniel M.; Strehlow, Sean; Chisum, Audrey M.; Dougherty, Kevin D.; Glanzer, Perry; Schnitker, Sarah A.
Abstract: Athletics occupies an ambiguous place within the greater university mission, particularly at religious institutions. Intercollegiate sports programs may purport to reinforce the university's aim to develop the whole person, but the nature of athletics can compromise student-athlete religiosity and well-being. Little research has focused on the religiosity of student-athletes and the potential implications for religious institutions. Our analysis features data from 884 senior students at a private, religiously affiliated, NCAA Division I university. Comparing student-athletes to non-athletes, we found that student-athletes scored higher than non-athletes on religious beliefs, religious behaviors, and sense of religious identity.